The Wage Return to Education: What Hides Behind the Least Squares Bias? - Corrado Andini (Institute for the Study of Labor (IZA), 2015)
This paper combines the approach by Guimar\~aes and Portugal (2010) with the methodology of Gelbach (2015) to investigate the determinants of the least squares bias of the wage return to education. We find that disregarding individual fixed effects is highly problematic, accounting for 95% of the bias. In contrast, disregarding firm fixed effects has marginal consequences.
Keywords: I21; J31; 330; wages; education; least squares